A New Species of Tacca Forst. from North East Frontier Agency, India - Deb, D. B. (Indian Forester, 1964)
Tacca choudhuriana Deb spec. nov. (Family: TACCACEAE) collected from the Subansiri Frontier Division of North East Frontier Agency, India, is described with illustrations. The specimen was collected and sent to the author of the paper for identification by Shri A.K. Choudhuri, Divisional Forest Officer, North East Frontier Agency after whom the speclftc name is installed.